Workplace Skills Development: A Multilevel Study of Jamaican Unattached Youth. (May 2016) - Chen, Danxia; Johnson, Ursula Y.; Hull, Darrell M.; Reid, Jon. K.
Youth are the future of a country and their workplace skills are vital for a society's growth and development. Unattached youth, neither at school nor at employment, pose a great challenge to the society. This study examines the impact of certain factors on unattached youth workplace skill development. Using a group of 322 unattached Jamaican youth who were recruited by the Jamaican National Youth Service, this study investigates certain individual differences such as five personality factors (openness, conscientiousness, extraversion, agreeableness, and neuroticism), cognitive ability, and gender's impact on workplace skills development among this group of Jamaican unattached youth using the multilevel modeling (MLM) analysis. The findings indicated that certain individual characteristics such as neuroticism and agreeableness have significant impact on their workplace skills development. Based on these results, career counseling and development should be considered to help unattached youth to develop their workplace skills to reach their potential.